The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpls.2022.829421
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus sinicus Incorporated as Green Manure for Weed Control in Corn

Abstract: Astragalus sinicus L. (milk vetch), one of the most widespread green manure species, is widely planted in the temperate zone. Eleusine indica L. (goosegrass), a serious annual weed in the world, has evolved resistance to some non-selective herbicides. The use of milk vetch as green manure for weed control in paddy fields was proposed. Aqueous extracts of milk vetch are known to exert a different level of phytotoxicity on weeds and crops. Phytotoxic substances contained in green manure were released into the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…The increase in EC at 12-h decomposition leachate was mainly due to the release of chemical elements from milk vetch, whereas the subsequent decrease may be due to the uptake of the elements by the colony and the chelation of certain elements such as manganese ions by organic substances such as oxalic acid and citric acid. The trend in EC changes was consistent with the findings of the previous study ( Liu et al., 2022 ). Researchers found that in the paddy-upland rotation system, milk vetch incorporation as green manure decreased soil pH value, which is consistent with the findings of this study ( Zhong et al., 2021 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The increase in EC at 12-h decomposition leachate was mainly due to the release of chemical elements from milk vetch, whereas the subsequent decrease may be due to the uptake of the elements by the colony and the chelation of certain elements such as manganese ions by organic substances such as oxalic acid and citric acid. The trend in EC changes was consistent with the findings of the previous study ( Liu et al., 2022 ). Researchers found that in the paddy-upland rotation system, milk vetch incorporation as green manure decreased soil pH value, which is consistent with the findings of this study ( Zhong et al., 2021 ).…”
Section: Resultssupporting
confidence: 92%
“…(Fabaceae), which reduced malondialdehyde (MDA) production by reducing lipid membrane peroxidation and restoring glutathione levels and the activity of catalase (CAT) and superoxide dismutase (SOD) ( Kondeva-Burdina et al., 2018 ). Previous studies have shown that the appropriate amount of milk vetch can increase the activity of the protective enzyme system and reduce the MDA content of maize ( Liu et al., 2022c ), which may be related to the increased total reducing the capacity of milk vetch during decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…Our study provided an overview of the developmental processes in FAWs fed on two different host plants, particularly on reproductive organ development. Goosegrass, an annual gramineous weed, is one of the major weeds in corn fields ( Liu et al, 2022 ), which can become an alternative plant host for the FAW when corn is not available. The development of S. frugiperda populations, including developmental time, embryonic development, and the fecundity level, differed on the two different host plants.…”
Section: Discussionmentioning
confidence: 99%
“…All residues significantly affected weeds' seedling emergence, dry weight, and vigour indices. Liu et al [43] observed that using Astragalus sinicus L. as green manure significantly reduced the germination and growth of E. indica; on the contrary, it favoured the growth of maize in a pot experiment. Some synergistic effects between allelopathic cover crops have been reported.…”
Section: Allelopathic Cover Crops For Weed Controlmentioning
confidence: 99%